1994
DOI: 10.1063/1.868147
|View full text |Cite
|
Sign up to set email alerts
|

Shear-induced particle migration in Couette and parallel-plate viscometers: NMR imaging and stress measurements

Abstract: Couette and parallel plate viscometers are two commonly used flow geometries to characterize shear viscosity of concentrated suspensions. In Couette flow, it is well documented that prolonged shearing causes a decrease in the apparent viscosity of concentrated suspensions due to shear-induced particle migration from the annulus region to the stagnant region under the bob. In this study, the technique of nuclear magnetic resonance imaging (NMRI) was used to measure the evolution of suspension concentration prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(103 citation statements)
references
References 11 publications
9
91
1
Order By: Relevance
“…Blood shows remarkable non-Newtonian effects primarily caused by RBC -RBC interactions and RBC -protein interactions: the aggregation and disaggregation of RBCs and their deformation dictate the value of viscosity [1,2]. A wide body of experimental evidence shows that flowing suspensions of rigid and deformable particles exhibit particle migration [3][4][5][6][7][8][9][10] with a general trend showing migration from regions of higher shear rate to regions of lower shear rate. RBCs also show this behaviour and their migration to the centre of micro and small vessels (micrometre to millimetre size) and the consequent segregation of PLTs near the wall has been the subject of intense study in the past years, both numerically [11][12][13][14] and experimentally [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Blood shows remarkable non-Newtonian effects primarily caused by RBC -RBC interactions and RBC -protein interactions: the aggregation and disaggregation of RBCs and their deformation dictate the value of viscosity [1,2]. A wide body of experimental evidence shows that flowing suspensions of rigid and deformable particles exhibit particle migration [3][4][5][6][7][8][9][10] with a general trend showing migration from regions of higher shear rate to regions of lower shear rate. RBCs also show this behaviour and their migration to the centre of micro and small vessels (micrometre to millimetre size) and the consequent segregation of PLTs near the wall has been the subject of intense study in the past years, both numerically [11][12][13][14] and experimentally [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…4) These experiments were for the determination of the material index, m, of the Krieger rheological model where φ c was assumed to be 0.68. However, for this present investigation, the fluid was non-Newtonian.…”
Section: Methodsmentioning
confidence: 99%
“…14) For the determination of the material constant, m in Equation (2), it is important to carry out experiments under the conditions that there is no or minimum particle migration. As it was shown that parallel-plate viscometer introduced little migration 4) , m was determined to be 0.82 using this testing method. Phillips et al 3) hypothesized that migration occured due to irreversibility in two-body interactions attributed to particle surface roughness, leading to constant empirical …”
Section: Rheological Predictionsmentioning
confidence: 99%
See 2 more Smart Citations